2008
DOI: 10.1016/s1473-3099(08)70017-3
|View full text |Cite
|
Sign up to set email alerts
|

Sustained reduction of antibiotic use and low bacterial resistance: 10-year follow-up of the Swedish Strama programme

Abstract: Resistance) was therefore started in 1994 to provide surveillance of antibiotic use and resistance, and to implement the rational use of antibiotics and development of new knowledge. Between 1995 and 2004, antibiotic use for outpatients decreased from 15·7 to 12·6 defined daily doses per 1000 inhabitants per day and from 536 to 410 prescriptions per 1000 inhabitants per year. The reduction was most prominent in children aged 5-14 years (52%) and for macrolides (65%). During this period, the number of hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
174
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(186 citation statements)
references
References 35 publications
3
174
0
5
Order By: Relevance
“…11,12 To our best knowledge, the present study is the first to correlate culture findings for the nasopharynx, and for the nasal middle meatus sampled via anterior rhinoscopy, with those for the maxillary antrum. The results indicate that bacterial findings for the maxillary antrum correlate slightly better with those for middle meatal secretions than those for the nasopharynx.…”
Section: Discussionmentioning
confidence: 78%
“…11,12 To our best knowledge, the present study is the first to correlate culture findings for the nasopharynx, and for the nasal middle meatus sampled via anterior rhinoscopy, with those for the maxillary antrum. The results indicate that bacterial findings for the maxillary antrum correlate slightly better with those for middle meatal secretions than those for the nasopharynx.…”
Section: Discussionmentioning
confidence: 78%
“…Long term follow up data from a national programme in Sweden showed no correlation between a reduction in outpatient antibiotic prescriptions for respiratory infections and selected complication rates. 27 Recent publications have highlighted the potential benefit of delayed antibiotic strategies in uncomplicated acute respiratory infections in adults. 28,29 These strategies are a compromise between the clinician's desire (and the patient's request) to 'do something' and to allay fears of missing potential complications on the one hand and the goal of reducing the possible consequences of antibiotic misuse on the other.…”
Section: Dn Williamsmentioning
confidence: 99%
“…15 In the current study, we found that antibiotic treatment was common, despite national programmes to reduce its use. 20 The most recent Cochrane update emphasised that antibiotics have a limited treatment effect in acute rhinosinusitis and stated that most cases will resolve without antibiotics within 2 weeks. 21 Our interpretation of the data is that, in contrast to medical evidence and recent guidelines, there still seems to be a general view among GPs that mild to moderate acute rhinosinusitis is the result of a bacterial infection.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 99%